261 HIGH FRACTURE RISK IN OLDER IRISH ADULT FALLERS. (25th October 2022) - Breslin, L; Bradley, E; Fitzpatrick, D; Laird, E; Hoey, L; Hughes, C; McNulty, H; Strain, JJ; Ward, M; Tracey, F; Molloy, A; Cunningham, C; et al.
Abstract: Background: Fracture risk due to falls depends on several factors including bone density, quality and size, hip geometry (axis length), direction of fall (forward, backwards or sideways), body mass index (BMI), type of surface impacted, body site of impact and mechanism of fall (eg syncope). We aimed to identify the fracture risk per fall in frail older Irish adults. Methods: Participants were from the hypertensive and cognitive cohort of the Trinity, Ulster, Dept Agriculture (TUDA) study of Irish adults (aged >60) recruited from hospital outpatient services and GP practises. Falls and falls resulting in fracture in the previous year were self-reported so those with an MMSE < 25 were excluded to avoid recall bias. We identified fallers, recurrent fallers and fractures due to falls in the previous year. Results: 892 fallers, mean age 76.3 ± 8.4 yrs, 65.2% female. 23.8% had 2 falls and 24.2% ≥3 falls. Mean timed up and go was 17.3 ± 9.5 seconds. Commonest fracture due to falls were hip (20.1%), upper limb (18.5%) and lower limb (17.9%) with one fracture of neck and skull. Fracture rate per fall was 7.1%: 1.7% for hip, 1.3% for lower and 1.2% for upper limb. Annual fracture rate per faller was 16.5%. The only predictors of fall with fracture versus no fracture were female sex (OR 2.4, 1.6-3.6, P<0.001) and lower body mass index (P=0.001). Conclusion: We identified similar hip fracture rates (1.7%) due to falls as in other studies. However, one in six fallers had sustained a fracture in the previous year reflecting the high proportion of recurrent fallers. Lower BMI and female sex predicted fall with fracture as both are strongly correlated with risk of osteoporosis. Recent guidelines now factor in recurrent falls when estimating the probability of future osteoporotic fractures.